The Relationship between Mindfulness and Social Entrepreneurial Intention with Perceived Behavioural Control as Mediator - Anh Bui Ngoc Tuan,; Loan Van Thi Hong,; Minh Pham, (Asian Academy of Management Journal, 2023)
There is in an ongoing conflict between economic development and social needs, especially in developing countries. Social enterprises have been seen as a key to solving this problem. Universities however, has not focused much social entrepreneurship as an academic course, unlike corporate social responsibility. The aim of this study therefore, was to examine the relationship between mindfulness and social entrepreneurial intention (SEI) and the intermediary role of perceived controllability and self-efficacy to generate ideas for academics to develop new generations of social entrepreneurs. The study used structural equation modelling (SEM) to test the research hypotheses. A total of 294 students at all academic levels (bachelor, master, and PhD) at selected universities in southern Vietnam participated in this study. The data was collected between August 2019 and October 2019 by using questionnaires. The results showed a positive relationship between mindfulness and SEI.. Additionally, the study noted students’ perceived controllability and especially self-efficacy can enhance this relationship.